Soil quality reflects microbial resource availability and drives rhizosphere microbiome variation in Ghanaian cocoa farms - Schmidt, J.; Addo-Danso, S.D.; Asare, R.; Tettey, A.; Isaac, M.E. (Elsevier, 2024)
Cocoa (Theobroma cacao L.) is an important crop in Ghana and the source of livelihood for hundreds of thousands of smallholder farmers. Maintaining soil quality on these farms is critical to ensuring the long-term viability of cocoa farming and preventing deforestation to meet rising demand. However, increasing attention to soil health has revealed a significant knowledge gap related to the soil microbiome in cocoa production systems. Using a nested design of sixteen smallholder cocoa farms in agroforestry or monoculture, on different soil quality classes and in different agroecological zones, a study was conducted to identify 1) drivers of rhizosphere microbial diversity and community composition across scales and 2) the extent of microbial differentiation between soil quality classes. Soil quality had far greater impacts than agroecological zone or agroforestry vs. monoculture management on microbial diversity and community composition, accounting for 17 % of variation in prokaryotes and 10 % in fungi. Good-quality and poor-quality soils contrasted in soil and root parameters, creating variable microbial resources, which led to differences in microbial community composition and the relative abundance of specific taxa. Soil organic matter and root traits were key drivers of community composition in good-quality soils, while permanganate-oxidizable carbon was relatively more important in poor-quality soils. These results underscore the importance of considering rhizosphere microbial communities in assessments of soil quality and highlight taxa that may serve as biological indicators of soil health in cocoa agroforestry systems.